#TITLE_ALTERNATIVE# - Astutik (NIM 122 03 019), Wynda
Abstract: Down-hole Water Sink (DWS) is an effective technology to control water coning problem in oil wells which usually occurs in a strong water drive reservoir with good vertical communication. Using DWS, a vertical oil well is dually completed for oil production and water drainage with two completions separated with packer. When properly designed, water-free oil is produced from top completion while oil-free water will be produced from bottom completion. The main idea of this technology is to create a counterbalance pressure drawdown in water zone, so water coning can be prevented and water-free oil can be obtained at surface. This study involves experiments with computer simulation to model reservoir performances and to approximate the existence of water coning in dual completion well. A volumetric two dimensional radial 2D reservoir model with bottom aquifer is appropriate to simulate this condition. This computer-simulated reservoir is used to confirm oil recovery in DWS well considering several reservoir parameters which influence DWS performance. These parameters are oil and water rate, oil zone thickness, vertical anisotropy, absolute horizontal permeability, oil perforation interval-oil zone thickness ratio, and water-oil mobility ratio. The objective of this study is to know the influence of parameters above to the DWS operation using sensitivity analysis and develop a correlation to obtain the best combination of oil and water rate to obtain maximum oil recovery. It also provides inflow performance window (IPW) plot to decide whether the oil and water rate combination should cause water coning, reversed coning, or segregated inflow. These will be used as a guideline for DWS design to select the optimum conditions, maximum oil recovery and water-free oil production at surface.